(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3GdecJHI GdebOejI HOeTb s)
(3ChdgG (B:s
(3gPG eG GNJGQg CHhJeGe MHjH Hf ChS GdWGFj ef GdMeGSI hgj GdTLGYI HGH GdMeGSI s
(3BNQgG (B:s
(3Ydi fZGfZ SGdJ aj jdGYegG cKjQI GdhTi aj djf hJQajb cCfeG djSJ Ch CdHSJ afcG abdUJ MhGTjg Yf GdShb s
(3GdfSNI HgG MhGTs
(3HMhGTj GdfSNI TQhM cKjQIs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs